Poetics of Rage : A Reading of Remi Raji's Poetry - Sule, E. E. (Emmanuel E.), 1976- (Book collections on Project MUSE., 2015)
This study explores the nationalist imagination, artistic philosophy and the overtly political dimension of Remi Raji's poetry. It is an attempt to construct a sustained critical discourse on Raji's ongoing body of works. Raji is one of the major poetic voices on the Nigerian literary scene today. With the publication of his first collection, A Harvest of Laughters, in 1997 Raji has continued to strengthen his craft and vision through subsequent volumes: Webs of Remembrance (2000), Shuttlesongs: America - a Poetic Guided Tour (2003), Lovesong for My Wasteland (2005); and Gather My Blood Rivers of Song (2009). Evidently he has attained poetic maturity and, given the frequency of his output, is set to realise a fulfilled poetic career. His maturation thus far through these five volumes deserves a major critical assessment, and a possible prediction for the direction of his artistic vision.